IMPROVING STUDENTS’ SPEAKING ABILITY IN GIVING INFORMATIVE SPEECH BY USING VISUAL AIDS - Dailin Dailin (English Education Study Program Faculty of Teacher Training and Education, 2017)
ABSTRACT The aim of this study was to improve the ability of students who took public speaking lesson on sixth semester at English study program of IAIN Bengkulu in giving an informative speech. The research method was classroom action research by doing three cycles. The respondents of this research were the students in public speaking class on sixth semester at English study program of IAIN Bengkulu. They were 21 students. The students who had enough ability in giving informative speech increased in each phase, 33.33% in cycle 1, 52.38% in cycle 2 and 57.14% in cycle 3. It meant some of students could increase their ability from very low or low to enough. In addition, the number of students who had enough ability in post-test decreased, it was 47.61%. That was because some of them could reach the higher ability such as good and very good. It showed that the students’ could decrease the difficulties in giving an informative speech. It meant the using of visual aids can improve the students’ ability in giving an informative speech.